Erasmus, Man of Letters : The Construction of Charisma in Print - Jardine, Lisa (Book collections on Project MUSE., 1993)
The name Erasmus of Rotterdam conjures up a golden age of scholarly integrity and the disinterested pursuit of knowledge, when learning could command public admiration without the need for authorial self-promotion. Lisa Jardine, however, shows that Erasmus self-consciously created his own reputation as the central figure of the European intellectual world. Erasmus himself-the historical as opposed to the figural individual-was a brilliant, maverick innovator, who achieved little formal academic recognition in his own lifetime. What Jardine offers here is not only a fascinating study of Erasmu.